Homologous genes shared between probiotics and pathogens affect the adhesion of probiotics and exclusion of pathogens in the gut mucus of shrimp - Sha, Yujie; Yan, Qingyun; Liu, Jian; Yu, Jiafeng; Xu, Shicai; He, Zhili; Ren, Jing; Qu, Jie; Zheng, Shiying; Wang, Guomin; Dong, Weiying (Frontiers in Microbiology, 2023)
Clarifying mechanisms underlying the selective adhesion of probiotics and competitive exclusion of pathogens in the intestine is a central theme for shrimp health. Under experimental manipulation of probiotic strain (i.e., Lactobacillus pentosus HC-2) adhesion to the shrimp mucus, this study tested the core hypothesis that homologous genes shared between probiotic and pathogen would affect the adhesion of probiotics and exclusion of pathogens by regulating the membrane proteins of probiotics. Results indicated that the reduction of FtsH protease activity, which significantly correlated with the increase of membrane proteins, could increase the adhesion ability of L. pentosus HC-2 to the mucus. These membrane proteins mainly involved in transport (glycine betaine/carnitine/choline ABC transporter choS, ABC transporter, ATP synthase subunit α atpB, amino acid permease) and regulation of cellular processes (histidine kinase). The genes encoding the membrane proteins were significantly (p < 0.05) up-regulated except those encoding ABC transporters and histidine kinases in L. pentosus HC-2 when co-cultured with Vibrio parahaemolyticus E1, indicating that these genes could help L. pentosus HC-2 to competitively exclude pathogens. Moreover, an arsenal of genes predicted to be involved in carbohydrate metabolism and bacteria-host interactions were identified in L. pentosus HC-2, indicating a clear strain adaption to host’s gastrointestinal tract. This study advances our mechanistic understanding of the selective adhesion of probiotics and competitive exclusion of pathogens in the intestine, and has important implications for screening and applying new probiotics for maintaining gut stability and host health.